2022
DOI: 10.1371/journal.pone.0263679
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 seroprevalence in the city of Puerto Madryn: Underdiagnosis and relevance of children in the pandemic

Abstract: Background Reported cases of COVID-19 may be underestimated due to mild or asymptomatic cases and a low testing rate in the general population. Research question What is the seroprevalence of SARS-CoV-2 infection in the general population and how it compares with the data on SARS-CoV-2 cases reported by a national health surveillance system (SNVS 2.0). Study design and methods This was a population-based, seroepidemiological, cross-sectional study in the city of Puerto Madryn, a middle size city in the Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…After Delta emergence, the proportion of pediatric COVID-19 tests have increased as conditions for testing were extended [4]. The reported case surveillance data in children, based on molecular or antigen testing, underestimate the overall burden of COVID-19, as only a small proportion of acute infections are symptomatic, diagnosed, and reported [5].…”
Section: Introductionmentioning
confidence: 99%
“…After Delta emergence, the proportion of pediatric COVID-19 tests have increased as conditions for testing were extended [4]. The reported case surveillance data in children, based on molecular or antigen testing, underestimate the overall burden of COVID-19, as only a small proportion of acute infections are symptomatic, diagnosed, and reported [5].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Numerous seroprevalence studies have been conducted in the Latin American region, both population-based studies and studies focusing on specific populations (healthcare (HCW) or first-line workers, prison workers, indigenous populations, elderly populations, etc). [4][5][6][7][8][9][10][11][12][13][14][15] The reported seroprevalence is highly heterogenous between studies (10,4% -68,1 %), varying by study population, characteristics of the COVID-19 epidemic at the time of sampling, and differences in sociodemographic factors. [4][5][6][7][8][9][10][11][12][13][14][15] Factors associated with increasing risk of seropositivity include ethnicity (indigenous or Afro-descent), presence of COVID-19 symptoms, past history of COVID-19 or close contacts, lower educational level, and working night shifts (for HCW) or in a prison.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Numerous seroprevalence studies have been conducted in the Latin American region, both population-based studies and studies focusing on specific populations (healthcare (HCW) or first-line workers, prison workers, indigenous populations, elderly populations, etc). [4][5][6][7][8][9][10][11][12][13][14][15] The reported seroprevalence is highly heterogenous between studies (10,4% -68,1 %), varying by study population, characteristics of the COVID-19 epidemic at the time of sampling, and differences in sociodemographic factors. [4][5][6][7][8][9][10][11][12][13][14][15] Factors associated with increasing risk of seropositivity include ethnicity (indigenous or Afro-descent), presence of COVID-19 symptoms, past history of COVID-19 or close contacts, lower educational level, and working night shifts (for HCW) or in a prison.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15] The reported seroprevalence is highly heterogenous between studies (10,4% -68,1 %), varying by study population, characteristics of the COVID-19 epidemic at the time of sampling, and differences in sociodemographic factors. [4][5][6][7][8][9][10][11][12][13][14][15] Factors associated with increasing risk of seropositivity include ethnicity (indigenous or Afro-descent), presence of COVID-19 symptoms, past history of COVID-19 or close contacts, lower educational level, and working night shifts (for HCW) or in a prison. [4][5][6][7][8][9][10][11][12][13][14][15] Among these studies, a cross-sectional study in 2020 of 3,124 children aged 5 to 17 years in 10 Colombian cities reported highly variable seroprevalence ranging from 25.0% in Medellin to 63.9% in Guapi, the latter a coastal city with a high proportion of Afro-Colombians with the poorest living conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation